Burkholder–Davis–Gundy Inequalities in UMD Banach Spaces - Yaroslavtsev, Ivan (Communications in mathematical physics, 2020)
In this paper we prove Burkholder–Davis–Gundy inequalities for a general martingale M with values in a UMD Banach space X . Assuming that M 0 = 0 , we show that the following two-sided inequality holds for all 1 ≤ p < ∞ : Here γ ( [ [ M ] ] t ) is the L 2 -norm of the unique Gaussian measure on X having [ [ M ] ] t ( x ∗ , y ∗ ) : = [ ⟨ M , x ∗ ⟩ , ⟨ M , y ∗ ⟩ ] t as its covariance bilinear form. This extends to general UMD spaces a recent result by Veraar and the author, where a pointwise version of ( ⋆ ) was proved for UMD Banach functions spaces X . We show that for continuous martingales, ( ⋆ ) holds for all 0 < p < ∞ , and that for purely discontinuous martingales the right-hand side of ( ⋆ ) can be expressed more explicitly in terms of the jumps of M . For martingales with independent increments, ( ⋆ ) is shown to hold more generally in reflexive Banach spaces X with finite cotype. In the converse direction, we show that the validity of ( ⋆ ) for arbitrary martingales implies the UMD property for X . As an application we prove various Itô isomorphisms for vector-valued stochastic integrals with respect to general martingales, which extends earlier results by van Neerven, Veraar, and Weis for vector-valued stochastic integrals with respect to a Brownian motion. We also provide Itô isomorphisms for vector-valued stochastic integrals with respect to compensated Poisson and general random measures.